Genetic variation associated with chromosomal aberration frequency: A genome-wide association study - Niazi, Yasmeen; Thomsen, Hauke; Smolkova, Bozena; Vodickova, Ludmila; Vodenkova, Sona; Kroupa, Michal; Vymetalkova, Veronika; Kazimirova, Alena; Barancokova, Magdalena; Volkovova, Katarina; Staruchova, Marta; Hoffmann, Per; et al. (Environmental and molecular mutagenesis, 2019)
Chromosomal aberrations (CAs) in human peripheral blood lymphocytes (PBL) measured with the conventional cytogenetic assay have been used for human biomonitoring of genotoxic exposure for decades. CA frequency in peripheral blood is a marker of cancer susceptibility. Previous studies have shown associations between genetic variants in metabolic pathway, DNA repair and major mitotic checkpoint genes and CAs. We conducted a genome-wide association study on 576 individuals from the Czech Republic and Slovakia followed by a replication in two different sample sets of 482 (replication 1) and 1288 (replication 2) samples. To have a broad look at the genetic susceptibility associated with CA frequency, the sample sets composed of individuals either differentially exposed to smoking, occupational/environmental hazards, or they were untreated cancer patients. Phenotypes were divided into chromosome- and chromatid-type aberrations (CSAs and CTAs, respectively) and total chromosomal aberrations (CAtot). The arbitrary cutoff point between individuals with high and low CA frequency was 2% for CAtot and 1% for CSA and CTA. The data were analyzed using age, sex, occupation/cancer and smoking history as covariates. Altogether 11 loci reached the P-value of 10-5 in the GWAS. Replication 1 supported the association of rs1383997 (8q13.3) and rs2824215 (21q21.1) in CAtot and rs983889 (5p15.1) in CTA analysis. These loci were found to be associated with genes involved in mitosis, response to environmental and chemical factors and genes involved in syndromes linked to chromosomal abnormalities. Identification of new genetic variants for the frequency of CAs offers prediction tools for cancer risk in future. Environ. Mol. Mutagen. 60:17-28, 2019. © 2018 Wiley Periodicals, Inc.
Keywords: celogenomová asociační studie; Česká republika; promotorové oblasti (genetika); Polymorphism, Single Nucleotide; poškození DNA; Female; DNA Repair; chromozomální aberace; Cytogenetic Analysis; Humans; Autistic Disorder; genetická predispozice k nemoci; Slovakia; autistická porucha; lidé středního věku; cytogenetické vyšetření; Genome-Wide Association Study; Czech Republic; Slovenská republika; Promoter Regions, Genetic; Down Syndrome; Neoplasms; lidé; mužské pohlaví; Genetic Predisposition to Disease; Chromosome Aberrations; dospělí; oprava DNA; Male; ženské pohlaví; Downův syndrom; DNA Damage; Adult; Middle Aged; nádory; jednonukleotidový polymorfismus